(untitled) (Bangladesh Journal of Animal Science, 2016)
This study was designed to adopt in vitro embryo production (IVP) protocol using abattoir ovary. Ovaries were collected from local abattoir; cumulus-oocyte-complexes (COCs) were aspirated from 3 to 8 mm diameter follicles using a 10 ml disposable syringe attached with a 21G needle. The COCs were selected based on morphological characteristics and selected COCs were transferred into in vitro maturation (IVM) medium for 22 to 24 hrs. The matured COC were fertilized in vitro (IVF) using fresh semen capacitated through incubation with heparin sodium salt (20 ?g/ml). After IVF, the presumed denuded zygotes were cultured in in vitro culture medium-I (IVC-I) for 3 days. After 3 days, the ?8 cell embryos were transferred into IVC-II medium until day 8 of embryonic development (day 0: day of IVF). Cleavage and blastocyst development rates were evaluated at day 3 and day 7. The maturation rates of COC were examined through detection of first polar body and cumulus cell expansion. Results showed that 74.16 ± 5.49% of the total immature COCs were matured as detected by the presence of first polar body. The diameter of matured COC was 2.21 times higher than that of the immature COC. Moreover, about 64.30 ± 6.71% COC showed full expansion of their cumulus cell. The cleavage rate of presumed zygotes was 62.05 ± 7.07%. Among the cleaved embryos, 26.67 ± 11.78%, 10.84 ± 6.13%, 22.51 ± 9.57% and 39.98 ± 5.25% embryos were at 2-, 4-, 8- and 16 to 32-cell embryonic stages, respectively at day 3. Blastocyst development rates were 14.95 ± 4.39%. This study inferred that the BLRI adopted culture system supports development of bovine embryo in vitro. Bang. J. Anim. Sci. 2016. 45 (1): 31-35